Methods for assesing population size in sand dune lizards (Liolaemus multimaculatus) - Kacoliris, Federico Pablo (2009)
Basic information, such as population size and density, is needed for conservation and management of many species, especially threatened species. Thus, well-designed population monitoring programs that use appropriate methods for estimating parameters of interest, including density and survival, are needed as well. Mark-recapture and distance-sampling are established methods for estimating density in wildlife surveys. The sand dune lizard (Liolaemus multimaculatus) is an endemic and vulnerable species that inhabits dune habitats in Argentina. At present, however, there are no accurate estimates of density of this species and no established monitoring programs. The objectives of this study were (1) to test the use of markrecapture and distance-sampling methods and (2) to estimate density of this species in Mar Chiquita Reserve (37u 379 S–57u 169 W), an important area for the protection of this species. For distance-sampling surveys, we used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. inhabits dune habitats in Argentina. At present, however, there are no accurate estimates of density of this species and no established monitoring programs. The objectives of this study were (1) to test the use of markrecapture and distance-sampling methods and (2) to estimate density of this species in Mar Chiquita Reserve (37u 379 S–57u 169 W), an important area for the protection of this species. For distance-sampling surveys, we used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. inhabits dune habitats in Argentina. At present, however, there are no accurate estimates of density of this species and no established monitoring programs. The objectives of this study were (1) to test the use of markrecapture and distance-sampling methods and (2) to estimate density of this species in Mar Chiquita Reserve (37u 379 S–57u 169 W), an important area for the protection of this species. For distance-sampling surveys, we used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. Liolaemus multimaculatus) is an endemic and vulnerable species that inhabits dune habitats in Argentina. At present, however, there are no accurate estimates of density of this species and no established monitoring programs. The objectives of this study were (1) to test the use of markrecapture and distance-sampling methods and (2) to estimate density of this species in Mar Chiquita Reserve (37u 379 S–57u 169 W), an important area for the protection of this species. For distance-sampling surveys, we used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard. u 379 S–57u 169 W), an important area for the protection of this species. For distance-sampling surveys, we used a systematic line-transect design; for mark-recapture sampling, we performed exhaustive surveys and captured, marked, and recaptured lizards manually. Based on distance-sampling, populations were estimated at 3.6 and 5.4 individuals per ha in 2007 and 2008, respectively; corresponding estimates based on markrecapture data were 5.2 and 4.1 individuals per ha in 2007 and 2008, respectively. Detection probabilities were 0.23 in both 2007 and 2008 distance-sampling analyses and capture probabilities were 0.02 and 0.05 in 2007 and 2008 mark-recapture analyses. Based on these estimates, the Mar Chiquita Reserve contains a population of at least 10,000 individuals. Both methods were adequate for estimating populations of sand dune lizards, given the facility with which individuals can be detected and captured. The distance-sampling method requires less effort, but the mark-recapture method allows estimates of survival as well as density. Results of this work provide the baseline for developing a monitoring program for this lizard, and we suggest that the distance-sampling method be used to monitor all populations of sand dune lizard.